Academic supervision assistance to "improve" the preparation of instructor learning outcomes tests - Rani Darmayanti (Jurnal Dedikasi, 2022)
The study challenge pertains to the potential efficacy of academic supervision in enhancing the pedagogical competencies of high school teachers, specifically in the context of developing learning outcome assessments. The objective of this study is to improve the proficiency of high school teachers in the development of reviews for learning objectives. The employed approach involves utilizing school action research, encompassing four distinct stages. This research covers three variables: the Input Variable, which pertains to the teacher's competence in designing evaluation tests for learning outcomes; the process variable, which involves the implementation of continuous academic supervision; and the output variable, which focuses on the enhancement of teacher performance in the context of learning. The researcher employed a method of data analysis known as comparative descriptive analysis. The findings derived from the study of the data indicate a noticeable improvement in the proficiency of high school teachers in developing learning outcome assessments during both cycle I and cycle II. The demonstration of this phenomenon is evidenced by the findings of observations conducted to assess teachers' proficiency in developing assessments for learning objectives within each instructional cycle.